Pelatihan Microsoft Word 2007 untuk Guru SMA St Bellarminus Bekasi sebagai Sarana Pendukung Proses Pembelajaran di Sekolah - Ziveria , Mira; Ridha Sefina Samosir; Sumbogo, Ignatius Ario; Siti Ruhana Dara; Salman (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2025)
Microsoft Word 2007 training for teachers of SMA St Bellarminus Bekasi aims to improve technological skills in compiling learning documents, class administration, and increasing teacher efficiency and productivity in daily work. Microsoft Word 2007, with advanced features such as Ribbon, SmartArt, Tables, Styles, Track Changes, and Mail Merge, makes it easy for teachers to create interesting teaching materials, compile exam questions, manage student data, and collaborate with colleagues. This training is designed to equip teachers with practical skills in using various Microsoft Word 2007 features that are relevant to educational needs, both in compiling administrative documents and class management. By mastering Microsoft Word 2007, teachers are expected to save time in completing administrative tasks, improve the quality of teaching materials, and support more effective and efficient teaching activities.